Achievements of the Australian Access to Allied Psychological Services (ATAPS) program: summarising (almost) a decade of key evaluation data. Issue 1 (December 2016) - Bassilios, Bridget; Nicholas, Angela; Reifels, Lennart; King, Kylie; Fletcher, Justine; Machlin, Anna; Ftanou, Maria; Blashki, Grant; Burgess, Philip; Pirkis, Jane
Abstract Background Introduced in July 2001, Australian Access to Allied Psychological Services (ATAPS) was the inaugural national policy initiative to provide community access to government-funded psychological services in primary care. Our aim was to examine the achievements of ATAPS in relation to its stated objectives using a set of indicators that largely drew on data from a minimum data set that we designed for the evaluation of ATAPS. Methods We used de-identified professional-, consumer- and session-level data from the minimum dataset, and secondary analyses of our quantitative and qualitative data collected for a series of specific evaluation studies. Available data covered the period from 1 July 2003 to 31 December 2012. Results Approximately 350, 000 referrals were made to the ATAPS program over the 9.5 year analysis period, 79 % of which resulted in services. Over 1.4 million sessions were offered. Overall, 29 % of consumers were male, 4 % children, and 3 % Aboriginal people; 54 % of consumers had depression and 41 % an anxiety disorder; at least 60 % were on low incomes; and around 50 % resided outside of major cities. The most common interventions delivered were cognitive and behavioural therapies. Selected outcome measures indicated improvement in mental health symptoms. Conclusions Access to Allied Psychological Services achieved its objectives within a decade of operation. The program delivered evidence-based services to a substantial number of consumers who were disadvantaged and historically would not have accessed services. Importantly, where data were available, there were indications that ATAPS achieved positive clinical outcomes for consumers. This suggests that ATAPS carved an important niche by successfully addressing unmet need of hard-to-reach consumers and through means that were not available via other programs. It will be interesting to see the effects from July 2016 of the reform of ATAPS, which will see ATAPS subsumed under psychological services commissioned by regional primary care organisations.